Comparison of tumour biomarker HER-2/neu (C-erbB-2) before and after surgery in breast cancer patients - Aung, Sanda; Mohd Noor, Noriah; Mohammad Amjad, Nasser; Abdullah, Nasuruddin; Phyu, Htike Myat (2014)
Breast cancer is the most common cancer and a major cause of morbidity and mortality in women worldwide annually. The proto-oncogene Human Epidermal growth factor Receptor-2(HER-2/neu) (C-erbB-2) has been localized to chromosome 17q and encodes a transmembrane tyrosine kinase growth factor receptor. The activation of the Her-2/neu oncogene triggers a cascade of growth signals that results in gene activation, which contributes the uncontrolled growth and survival of cancer cells. Molecular biomarker of cerb-B2 (HER-2/neu) is the prognostic indicator to predict the outcome for women with breast cancer. The cross sectional descriptive study was carried out on 31 breast cancer patients admitted to Surgical Department, Hospital Tengku Ampuan Afzan, Kuantan for breast cancer operation, between January, 2012 and July, 2013. This study was approved by Medical research and Ethics Committee, Ministry of Health Malaysia and all the participants gave their written informed consent. The pre- and post-operative serum Her2/neu protein level in all types of breast cancer was measured by ELISA method. Histological grading was done according to Modified Bloom and Richardson Grading2. The data was analysed by using SPSS version 11.5. In 31 patients, the ages ranged from 38 to 77 years with a mean of 54 years. The mean serum concentrations of Her2/neu protein before and after operation were 1.88+1.527 ng/ml and 1.31+0.994) ng/ml, respectively. Paired Sample T test showed there is a significant correlation between pre- and post-operative serum level of Her2/neu (p=0.004). Mann Whitney U test analysis showed the pre-operative serum level of Her2/neu protein was associated with vascular invasion (p=0.009). However, there was no significant relation between prognostic biomarker Her2/neu and the clinical prognostic parameters of tumor size, lymph node involvement, lymphatic invasion, histological type and grade in all types of breast cancer. High HER-2/neu protein expression is associated with more ductal carcinoma in situ, invasive cancer, high cell proliferation rate, lack of response to hormone therapy, aggressive clinical behavior, development of metastasis, treatment resistance, cancer progression, decreased chance of survival and poor prognosis. However, Her2/neu overexpression tumours response to herceptin. Although the duration of study is short and the small size is small, serum Her2/neu protein level in breast cancer may predict the prognosis, response to therapy, and will be able to assist in breast cancer management.